Is endoscopic treatment beneficial in patients with clinically suspicious of common bile duct stones but no obvious filling defects during the ERCP examination?. Issue 1 (December 2016) - Chiang, Po-Hung; Lai, Kwok-Hung; Tsai, Tzung-Jiun; Lin, Kung-Hung; Wang, Kai-Ming; Kao, Sung-Shuo; Sun, Wei-Chih; Cheng, Jin-Shiung; Hsu, Ping-I; Tsai, Wei-Lun; Chen, Wen-Chi; Li, Yun-Da; et al.
Abstract Background Sometimes, no definite filling defect could be found by cholangiogram (ERC) during the endoscopic retrograde cholangio-pancreatiographic (ERCP) exam; even prior images had evidence of common bile duct stones (CBDS). We aimed in estimating the positive rate of extraction of CBDS who had treated by endoscopic sphincterotomy/endoscopic papillary balloon dilation (EST/EPBD) with negative ERC finding. Methods One hundred forty-one patients with clinically suspicious of CBDS but negative ERC, who had received EST/EPBD treatments was enrolled. Potential factors for predicting CBDS, as well as the treatment-related complications were analyzed. Results Nearly half of the patients with negative ERC, had a positive stone extraction. Only patients with high probability of CBDS were significantly associated with positive stone extraction. Moreover, patients with intermediate probability of CBDS had higher rates of overall complications, including post-ERCP pancreatitis. In addition, no significant difference of post-ERCP pancreatitis was found between EST and EPBD groups in any one group of patients with the same probability of CBDS. Conclusions Regarding patients with negative ERC, therapeutic ERCP is beneficial and safe for patients present with high probability of CBDS. Moreover, under the same probability of CBDS, there was no significance difference in post-ERCP pancreatitis between EST and EPBD.